Short- and long-term outcomes of aortic root-sparing repair and replacement in acute type A aortic dissection repair. (September 2021) - Tarkas, Tillana Nirav; Stoicescu, Carla; Munir, Wahaj; Bashir, Mohamad; Adams, Benjamin
Acute type A aortic dissection is a surgical emergency with a high mortality rate if left untreated. Management of the aortic root in this setting constitutes an intricate decision-making framework, further complicated by the emergent nature of the dissection. There exists much controversy regarding pursuit of the aggressive aortic root replacement versus a conservative root-sparing repair, alongside considerations for valve-sparing root replacement. In this review, we critically appraise the current controversy in the literature considering the fate of the aortic root, discussing the aforementioned root interventions for which provides better outcomes for mortality and risk of re-intervention. Literature search was performed using electronic database through PubMed, Google scholar, and Embase focussing on studies reporting outcomes and re-intervention rates for these approaches. Limited by the heterogeneity in surgical strategy, with most studies being single-centred retrospective experiences, further fuel this ongoing debate. The literature reveals rather contrasting results whilst comparing root-sparing repair, versus the extensive root replacement; whilst some studies report no statistically significant difference, others show one superior over the other. There is greater consensus when considering risk of re-operation, with studies showing higher rates of re-operation in root-sparing group compared to replacement; however, many others show no statistically significant difference. In conclusion, the conflicting outcomes reported in the literature, with their inherent limitations, results in the current inability to reach a definitive answer. There remains support in the current literature for both approaches with much of the decision-making being surgeon-bound with many significant influencing factors on a case-by-case basis.